Environmental liabilities calculation to increase three-dimensional accounting and integral sustainability in mining companies - Wong Figueroa, Bertha Leonor (2018)
In the balance of the company, the "liability" is the set of debts that are thoroughly analyzed and recorded for its counterpart with the "asset", there is a particular type of liability that is rarely accounted for: the "environmental liability" ", which is the summary of all the uncompensated damages produced directly and indirectly to the environment, which make productive activities possible. The economic valuation of environmental costs is difficult given that many goods are not interchangeable in the market, some characterized as intangible, for this reason the objective research was focused on the environmental liabilities estimates, through the applicable software to be accounted for. by the mining companies by Huánuco region, increasing three-dimensional accounting and integral sustainability. The study research is applied quantitative, qualitative, transversal, descriptive, correlational, explanatory, non-experimental, deductive, documentary and field research. The survey technique was used to collect the information. The results indicated that mining companies generate environmental liabilities that are not accounted for. It is concluded that the environmental liabilities calculations allow the integral sustainability of accounting in the environmental, social and economic dimensions.